2010
DOI: 10.1890/09-0855.1
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐mediated interactions and lifetime fitness of the invasive plant Centaurea solstitialis

Abstract: Plants interact with numerous enemies and mutualists simultaneously and sequentially. Such multispecies interactions can give rise to trait-mediated indirect effects that are likely to be common in nature but which are also inherently difficult to predict. Understanding multispecies interactions is also important in the use of biological control agents to control invasive plants because modern approaches to biocontrol rely on releasing multiple agents for each target weed. Centaurea solstitialis is one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Here, multiple agents are often introduced to reduce populations of a particular weed [12], and agents also must interact with native generalists. Two broad rationales exist for introducing multiple biological control agents [13]: (i) the lottery model predicts that the introduction of more agents will more probably involve a successful agent [12], while (ii) the cumulative stress hypothesis predicts increased plant suppression with more agents, as small amounts of damage by individual species accumulate [14]. If multiple biological control agents are introduced, it would be optimal to introduce agents that will interact synergistically and counterproductive to introduce antagonistic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Here, multiple agents are often introduced to reduce populations of a particular weed [12], and agents also must interact with native generalists. Two broad rationales exist for introducing multiple biological control agents [13]: (i) the lottery model predicts that the introduction of more agents will more probably involve a successful agent [12], while (ii) the cumulative stress hypothesis predicts increased plant suppression with more agents, as small amounts of damage by individual species accumulate [14]. If multiple biological control agents are introduced, it would be optimal to introduce agents that will interact synergistically and counterproductive to introduce antagonistic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In either case, additive or synergistic interactions among agents is possible and desirable. However, it is also possible for agents to interfere with one another, even when they never interact directly (Denno et al 1995, Swope andParker 2010a). In previous work, we found that infection by the foliar pathogen Puccinia jaceae f.s.…”
Section: Introductionmentioning
confidence: 72%
“…In previous work, we found that infection by the foliar pathogen Puccinia jaceae f.s. solstitialis, a newly released biocontrol agent, had a direct, negative impact on its host, the invasive plant Centaurea solstitialis, but infection also significantly reduced seed predation by the seed predator Eustenopus villosus, a well-established biocontrol agent (Swope and Parker 2010a). We hypothesized two possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations